ANALISIS PENGARUH STRES KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP TURNOVER INTENTION KARYAWAN - Cahyadinanto Sanjoko, Deny; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the effect of work stress variables and non-physical work environment on job satisfaction and its impact on employee turnover intention. This research was conducted at PT Panverta Cakrakencana Pandaan. The number of samples is set to a total of 100 respondents with a sampling using simple random sampling method. Measurements in the questionnaire using a Likert scale. Data analysis method that used in the research is Structural Equation Model (SEM) with the help of the AMOS 16.0 software.Results of hypothesis testing showed that the work stress variables and significant positive effect on employee turnover intention. Job stress negatively affects job satisfaction. Non-physical work environment positive effect on job satisfaction. Non-physical work environment negatively affect employee turnover intention. Job satisfaction negatively affect turnover intention. Path Analysis of the results showed that the direct effect of work stress and non-physical work environment to turnover intention of employees value is 0.226 and -0.335. The indirect effect of job stress and non-physical work environment on turnover intention through job satisfaction value is 0.095 and - 0.104.